The UMPSA Kembaran Prihatin Programme reaches out to the wider higher education community - Mimi Rabita, Abd Wahit (UMPSA, 2024)
TUARAN, 3 March 2024 - The Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) Kembara Prihatin Programme, involving 55 student volunteers and 15 staff, with almost 30 activities carried out since 27 February, succeeded in bringing the community closer to the university and benefiting the community in Sabah.